2013
DOI: 10.3892/ijmm.2013.1308
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the inhibition of PAI-1 by metal theaflavin complexes and their degradation products

Abstract: The inhibition of elements of the plasminogen activator system [urokinase (uPA), tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1)] plays an important role in human diseases. PAI-1 is overexpressed in obesity and diabetes, and the inhibition of this protein has been postulated to alleviate the symptoms of both disorders. We found that two theaflavins (TFs) from black tea inhibit PAI-1 and we suggest that the beneficial effects of drinking tea may be associated with the suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that TF can be oxidized to dehydrotheaflavin during model tea fermentation or under the presence of metal. [ 24–27 ] However, whether dehydrotheaflavin is the oxidized metabolite of TF in vivo and has the capacity to trap ammonia in mice are still unknown. Under the search of dehydrotheaflavin at m/z 577.0971 [M‐H] − , one peak appeared at 4.47 min in TF‐treated mouse fecal sample ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that TF can be oxidized to dehydrotheaflavin during model tea fermentation or under the presence of metal. [ 24–27 ] However, whether dehydrotheaflavin is the oxidized metabolite of TF in vivo and has the capacity to trap ammonia in mice are still unknown. Under the search of dehydrotheaflavin at m/z 577.0971 [M‐H] − , one peak appeared at 4.47 min in TF‐treated mouse fecal sample ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of in vitro and in vivo experiments are frequently conflicting (59). This may be related to poor EGCG bioavailability, its oxidation that starts during contact with air, gastrointestinal inactivation, liver metabolism, or hard water (27,59,60). The majority of clinical studies on human treatment with EGCG were carried out using the oral administration route (33,61,62).…”
Section: Discussionmentioning
confidence: 99%